2015
DOI: 10.1016/j.jcma.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Is there any role of latent toxoplasmosis in schizophrenia disease?

Abstract: In the study area with a high prevalence of T. gondii, no association between toxoplasmosis and schizophrenia was detected. These findings showed that toxoplasmosis has no role in the risk of schizophrenia disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…Previous studies from Iran arrived at inconsistent results regarding the association between schizophrenia and T. gondii seropositivity . Recent research from other countries failed to show a significant association between schizophrenia and T. gondii infection .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies from Iran arrived at inconsistent results regarding the association between schizophrenia and T. gondii seropositivity . Recent research from other countries failed to show a significant association between schizophrenia and T. gondii infection .…”
Section: Discussionmentioning
confidence: 96%
“… of 38 studies showed that individuals with schizophrenia have an increased prevalence of antibodies to T. gondii ; the overall odds ratio was 2.71 (95% CI: 1.93–3.80). However, other studies failed to demonstrate a significant association between schizophrenia and toxoplasmosis . Several investigators in various parts of Iran have sought to determine the association of schizophrenia with T. gondii seroprevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 2,604 different articles in English, French, Spanish, Portuguese, Chinese, and Russian, initially identified for co-morbidities between mental health and chronic physical diseases, and for comorbidities between mental health and neurotropic parasitic diseases, 18 articles were included in our meta-analysis ( Figure 1). Among these 18 articles of co-morbidity studies on mental disorders and neurotropic parasitic diseases [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] published between 1997 and 2016 and meeting our inclusion criteria, two were prevalence studies in individuals with neurotropic parasitic diseases who were screened for mental disorders, and sixteen were analytical studies in individuals with mental disorders who were screened for neurotropic parasitic diseases (Table 2 and Table 3).…”
Section: General Resultsmentioning
confidence: 99%
“…In contrast, some authors have questioned this association 24,25 . A recent meta-analysis reported a significant association between T. gondii infection as estimated by IgG antibodies and schizophrenia (odds ratio 1.81, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%